2014
DOI: 10.1371/journal.pntd.0002946
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and Characterization of Seminal Fluid Proteins in the Asian Tiger Mosquito, Aedes albopictus

Abstract: The Asian tiger mosquito (Aedes albopictus) is an important vector for pathogens that affect human health, including the viruses that cause dengue and Chikungunya fevers. It is also one of the world's fastest-spreading invasive species. For these reasons, it is crucial to identify strategies for controlling the reproduction and spread of this mosquito. During mating, seminal fluid proteins (Sfps) are transferred from male mosquitoes to females, and these Sfps modulate female behavior and physiology in ways tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 134 publications
2
69
0
1
Order By: Relevance
“…However, there are three transferred Ae. albopictus Sfps that have 68% identity with AAEL010824 over the entire length of the protein (Boes et al, 2014). This finding is interesting as Leahy (1965) showed that implantation of Ae.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are three transferred Ae. albopictus Sfps that have 68% identity with AAEL010824 over the entire length of the protein (Boes et al, 2014). This finding is interesting as Leahy (1965) showed that implantation of Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Sequences from predicted Ae. albopictus proteins were obtained from Boes et al (2014). Sequences from predicted Ae.…”
Section: Methodsmentioning
confidence: 99%
“…There is ample evidence that, across a wide range of taxa, Sfps do tend to diverge more quickly on averge than non-Sfp genes (e.g., Aguadé 1998Aguadé , 1999Begun et al 2000;Swanson et al 2001;Haerty et al 2007;Almeida and DeSalle 2008;Mancini et al 2011;Wong et al 2012;Wong and Rundle 2013;Boes et al 2014). However, this pattern is consistent not only with CFC and sexually antagonistic coevolution, but also with male-male competition and other forms of selection such as host-pathogen interactions .…”
Section: Interspecific Divergence In Sfp Sequencesmentioning
confidence: 99%
“…In some instances, both males and females produce the same proteins-transferred as Sfps in the case of the male. For example, Aedes albopictus males transfer the neuropeptide adipokinetic hormone-1 (AKH-1) to females during mating (Boes et al 2014). AKH-1 is also produced by female mosquitoes and mobilizes the release of carbohydrates from the fat body into the hemolymph in some species (Kaufmann and Brown 2008;Kaufmann et al 2009).…”
Section: Interspecific Divergence In Sfp Sequencesmentioning
confidence: 99%
See 1 more Smart Citation